Makna Budaya dalam Ungkapan Melayu Manado pada Transaksi Jual Beli di Pasar Karombasan - Palar, Dwianita Conny (Kajian Linguistik, 2015)
Marketis a place where the interaction between seller and buyer happened. Marketbecomes social media that connect the used language in communication betweenseller and buyer who exist in traditional market of Manado and come fromvarious etnics. The researcher see the language which is used by buyer andseller in their buyer selling transaction. This thing is interested to beinvestigated. The aim of this research are (1) to identify form  and meaning of expression in using of ManadoMalay language at the buying-selling transaction in Karombasan traditionalmarket, Manado, and (2) to explain cultural meaning which contained in the useof Manado Malay language at buying-selling transaction in Karombasantraditional Market, Manado. Thisresearch employed descriptive method with qualitaitve approach. In collectingthe data, the method of Listening and Speaking of Surdayanto (1993) is used.Listening method is firstly used by using Listening Technique. Secondtechniques which are used are Listening Speaking Involment and ListeningSpeaking Free Involvement. In analyzing the collected data, theories of Cook(1969), Chaer (2007) and Kridalaksana are used to classify the language form ofexpression that are found. Then to get the cultural meaning that contained inthe expression, theory of Foley (1997) is used. There were 48 informantsactively involved in this research.Inthis research, the researcher found 8 forms of word  classified into basic word, repetition wordand compound word, namely: fresco, bos tabuang-buang, baminya-minya, tandatangan, masa pohong and masa karbit, 3 phrases expressions are also found suchas, kuli kadongdong, kuli duriang, and ikang pegawai. Then, sentence forms ofexpressions that are found namely ‘Om ini, kurang mo kase abis’, ‘Ngana petomat pe warna sama deng warna spanyol’, ‘Tanta kiapa depe mata ikang somerah’. Throughthis research, it can be concluded that this cultural-meaning expressioncontains cultural meaning, both positive meanings such as fresh thinking, likehelping other people, respect each other, good attitude, behavior, knowing goodand meet cultural life, having competence and negative meanings, such as badbehaviour, talkactive, not creative and having no competence. Based on theconclusion, the researcher suggests to the next researcher, to be morecomprehensive related to the use of Manado Malay language expression indifferent background and contexts in order to get a whole description aboutexpressions system of Manado Malay language.  Keyword: The Cultural Meaning, Tradisional Market